Analysis of a health camp at a rural set up in Nepal - Karki, Chandrima; Karki, Chanda; Basnet, Rydam; Basnet Dixit, Punam; Rajak, Ashik (Journal of Kathmandu Medical College, 2021)
Background: In Nepal where there is lack of health facilities in rural areas, health camps play an important role in providing health services. It is important to analyse health camps to determine the area of need and further planning. An analysis of a multispecialty health camp was done in Aurahi of Mahottari district which is one of the most rural areas of Nepal. Objectives: To quantitatively determine the population utilising the multispecialty health along with the patients’ demographic data and major health problems present in the area.Methods: A descriptive cross sectional study was conducted among 2560 people attending a health camp organised during 19th to 25th December 2019. Information was collected using registers with consent. Ethical clearance for the study was obtained from the Institutional Review Committee (IRC). The data were entered and analysed in Microsoft Excel.Results: Two thousand five hundred and sixty people which comprised 8.06% of the total population of the municipality reached out for services at the health camp. The number and percentage of population attending respective speciality were Nutrition - 869 (33.93%), Dental - 429 (16.75%), Gynaecology - 398 (15.50%), Medicine - 268 (10.46%), Obstetrics - 218 (8.52%), non-specific symptoms - 152 (5.94%), Dermatology - 122 (4.77%), ENT - 82 (3.22%) and Surgery - 50 (1.97%) respectively.Conclusion: The study shows presence of significant unmet health needs in this rural district of Nepal due to the lack of basic health services in the region.